PENGARUH EFIKASI DIRI TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS XI SMA NEGERI 5 PONTIANAK - Hindayani, Kiki; Khosmas, F.Y.; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to be aware of the effect of self-efficacy on the economic learning performance of ips sophomores in the country of 5 Pontianak high school. Using an associative research method. A research form is ex post facto, with population 143 students, and a sample of 58 students. The data is fed with indirect communication techniques. Studies indicate that a student’s self-efficacy of social studies was 61,21% designed and the highest learning performance was owned by 46 students with a percentage of 79,31%. There is a positive influence for self-efficacy study on the achievement of social studies in XI IPS clas at the state high school of 5 Pontianak. Shown by the value of t count 11,813, showing the effect of free variables on bonded variables. When compared with the table t at the significance level of 0,05 for 2,003. To calculate the t is greater than the table t or 11,813>2,003, so Ha is accepted and Ho is not accepted. Simple linear regression computation acquired Y=53,367+0,304. The coefficient determinations from the research show how variable is to reflect on a student’s economic learning feat of 39%, while the rest is influenced by another factor. The conclusion of this study is that self-efficacy has a significant impact on the equesian science class’s learning achievement in 5 Pontianak high school. Keywords: Self Efficacy, Learning Achievement, Economic Learning